Efektivitas Sistem Transportasi Kering Tertutup pada Pengangkutan Benih Lele Dumbo (Clarias Gariepinus) - Sri Oetami Madyowati, Kusyairi Nurul Hayati (AGROKNOW, 2013)
Abstract. One of the sufficient promising fish cultivation is cat fish cultivation. Cat fish cultivation highly prolific due to easy to cultivation in land and finite springs with high spread density, cultivation technology is relative easy to be learned by the people, such their marketing are easy and required capital is low. The aim of this research are to gain anesthetizes temperature, anesthetizes duration and both combination for the best to producing highest longevity level of cat fish seed (Clarias gariepinus) in closed dry transportation system. Research design that employed is RAL Factorial (Factorial Complete Random Design). Treatment in this research are two factors, namely temperature (A Factor) consist of three degrees (12,16 and 18 oC) with notation (a1,a2, and a3) and anesthetizes duration (B Factor) consists of three degrees (20, 30 and 40 minutes) with notation (b1,b2, and b3). Combination of this treatment are (a1b1), (a1b2),(a2b1), (a2b2), (a3b1), (a3b2) and (a3b3), respectively of this treatment combination done three times, obtained 27 treatment combinations.The result indicating that anesthetize temperature have real effect toward longevity level of cat fish seed (Clarias gariepinus) size 7-9 cm in closed dry transportation system for 10 hours produce highest longevity level in 16Â°C, around 95.91%. The anesthetizes duration did not have real effect on longevity level of cat fish seed (Clarias gariepinus) for 10 hours but yielding highest longevity level 20 minutes, that is 86.76%. Combination (interaction) of temperature and anesthetizes duration have real effect on longevity level of cat fish seed (Clarias gariepinus) size 7-9 in closed dry transportation system for 10 hours and yield highest longevity level of cat fish seed (Clarias gariepinus) is temperature anesthetizes 16Â°C and anesthetizes duration 40 minutes, as many 98.89%.Kata kunci : Clarias gariepinus, kelangsungan hidup, suhu, sistem transportasi kering tertutup